Translating 2019 ACSM Cancer Exercise Recommendations for a Physiatric Practice: Derived Recommendations from an International Expert Panel. Issue 8 (1st September 2021) - Parke, Sara C.; Ng, Amy; Martone, Patrick; Gerber, Lynn H.; Zucker, David S.; Engle, Jessica; Gupta, Ekta; Power, Katherine; Sokolof, Jonas; Shapar, Sam; Bagay, Leslie; Becker, Bruce E.; et al.
Abstract: In 2018, the American College of Sports Medicine (ACSM) reconvened an international, multi‐disciplinary group of professionals to review pertinent published literature on exercise for people with cancer. The 2018 roundtable resulted in the publication of three articles in 2019. The three articles serve as an important update to the original ACSM Roundtable on Cancer, which convened in 2010. Although the focus of the three 2019 articles is on exercise, which is only one part of comprehensive cancer rehabilitation, the evidence presented in the 2019 ACSM articles has direct implications for physiatrists and other rehabilitation professionals who care for people with cancer. As such, the narrative review presented here has two primary objectives. First, we summarize the evidence within the three ACSM articles and interpret it within a familiar rehabilitation framework, namely the Dietz model of Cancer Rehabilitation, in order to facilitate implementation broadly within rehabilitation practice. Second, via expert consensus, we have tabulated relevant exercise recommendations for specific cancer populations at different points in the cancer care continuum and translated them into text, tables, and figures for ease of reference. Notably, the authors of this article are members of the Cancer Rehabilitation Physician Consortium (CRPC), a group of physicians who subspecialize in cancer rehabilitation medicine (CRM).